Analisis Pengaruh Pengungkapan Terhadap Information Asymmetry Dengan Discretionary Accruals Sebagai Variabel Moderating - Frinan Satria (Journal of Accounting and Management Innovation, 2021)
Abstract: Information asymmetry can harm users until discloser can solve it. The objective of the research was to analyze the influence of disclosure on information asymmetry by analyzing determinant fundamental disclosure. Disclosure is proxied by access to growth, firm size, firm value, complexity, institutional ownership, leverage, profitability, and public ownership with earning management as moderating variable. The research object was food and beverages companies listed in the Indonesian Stock Exchange in the period of 2010-2014. The samples were taken by using purposive sampling technique. The data were analyzed by using multiple linear regression analysis. The result of the research showed that, partially, access to growth had insignificant influence on information asymmetry. Institutional ownership and public ownership had positive and significant influence on information asymmetry, while firm size had negative but significant influence on information asymmetry. Simultaneously, the four independent variables had significant correlation with information asymmetry. Earning management as moderating variable strengthened the correlation between disclosure and information asymmetry.Keywords: Information Asymmetry, Disclosure, Earning Management, Window Dressing, Income Management